The Effect of Digital Payment on Consumptive Behavior at Indomaret in Pematangraya City - Adrian K. Tarigan; Jopinus Saragih; Mhd. Ramadhan; Yeni Trisna Purba (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The rapid development of digital payment technology has transformed consumer transaction patterns by providing faster, more convenient, and secure payment methods. The increasing use of digital payment systems in modern retail has raised concerns regarding their potential influence on consumers' purchasing behavior, particularly consumptive behavior. This study aims to examine the effect of Digital Payment on Consumptive Behavior among consumers shopping at Indomaret in Pematangraya City, Indonesia. A quantitative research approach with an associative design was employed using purposive sampling. Primary data were collected through structured questionnaires from 96 respondents who had experience using digital payment during shopping transactions. The collected data were analyzed using descriptive statistics, validity and reliability tests, Pearson Product-Moment correlation analysis, and hypothesis testing through the t-test with the assistance of IBM SPSS Statistics 26. The findings reveal that Digital Payment has a significant positive influence on Consumptive Behavior. The convenience, transaction speed, security, and promotional benefits offered by digital payment systems encourage consumers to conduct transactions more frequently and increase the likelihood of impulsive purchasing. The statistical analysis confirms that the proposed hypothesis is accepted, indicating a significant relationship between Digital Payment and Consumptive Behavior. This study contributes empirical evidence regarding digital payment adoption in a regional retail environment and provides practical implications for retailers, digital payment providers, and policymakers in promoting responsible digital financial services and consumer spending behavior.